Efeito do peso relativo das sementes paternas sobre as progênies de milho opaco-2 - Saraiva, Luiz Sérgio; Anderson, John C (Revista Ceres, 2025)
The F1 generation of diallel crosses between classes of different relative weights of seed of the variety Maya-50 was studied. The influence of these different weights was analyzed using the F1 of the crosses and their reciprocals in the determination of the average weight of opaque-2 seeds expressed as % of the normal on the same ear. The opaque seeds of the F2 generation always showed a lower weight than the normal seeds on the same segregating ear. The over-all average weight of opaque seeds was 83,91% of the weight of the normal seeds. The variation in relative weight of opaque seeds ranged from 76.64% (reciprocal of low X low) to 90.71% (reciprocal of high X high) thus demonstrating the possibility of selection for higher relative seed beginning with paternal seed of greater relative weight.